2017
DOI: 10.1039/c7nr02121f
|View full text |Cite
|
Sign up to set email alerts
|

Surface and grain boundary energy as the key enabler of ferroelectricity in nanoscale hafnia-zirconia: a comparison of model and experiment

Abstract: The unexpected ferroelectric properties of nanoscale hafnia-zirconia are considered to be promising for a wealth of applications including ferroelectric memory, field effect transistors, and energy-related applications. However, the reason why the unexpected ferroelectric Pca2 phase can be stabilized has not been clearly understood although numerous extensive theoretical and experimental results have been reported recently. The ferroelectric orthorhombic phase is not a stable phase under processing conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
258
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 297 publications
(280 citation statements)
references
References 71 publications
13
258
2
1
Order By: Relevance
“…−1 , for PMA and PDA, respectively, by multiplying the Boltzmann's constant. [17] Already in a polycrystalline form with the t-phase being dominant after the first RTA at 600 °C for 20 s, pristine HZO sample would only obtain the m-phase from the adequate distortion and phase transformation from the already present t-phase. As a result, higher amount of the t-/o-phase remained which resulted in the enhanced ferroelectric properties produced in several reports.…”
Section: Resultsmentioning
confidence: 99%
“…−1 , for PMA and PDA, respectively, by multiplying the Boltzmann's constant. [17] Already in a polycrystalline form with the t-phase being dominant after the first RTA at 600 °C for 20 s, pristine HZO sample would only obtain the m-phase from the adequate distortion and phase transformation from the already present t-phase. As a result, higher amount of the t-/o-phase remained which resulted in the enhanced ferroelectric properties produced in several reports.…”
Section: Resultsmentioning
confidence: 99%
“…[63] Instead, the Pmn2 1 polar o-phase was energetically more favorable compared to the experimentally observed Pca2 1 o-phase. [23] Thus, Batra et al [26] suggested that various factors including compressive strain and electric field need to be combined to stabilize the Pca2 1 o-phase. [23] Thus, Batra et al [26] suggested that various factors including compressive strain and electric field need to be combined to stabilize the Pca2 1 o-phase.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…[21] Therefore, multiple factors were suggested as origin of the stabilization of the ferroelectric phase. [23] In the latter study, it was confirmed that the o-phase can be stabilized within the nuclei formed during the atomic layer deposition (ALD) process, but the interface/grain boundary effect is not sufficient to stabilize the o-phase within the final grain size after annealing. [23] In the latter study, it was confirmed that the o-phase can be stabilized within the nuclei formed during the atomic layer deposition (ALD) process, but the interface/grain boundary effect is not sufficient to stabilize the o-phase within the final grain size after annealing.…”
mentioning
confidence: 96%
See 2 more Smart Citations